2021
DOI: 10.1002/jac5.1450
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist‐led optimization of heart failure medications: A systematic review

Abstract: Medications are a cornerstone of treatment of heart failure (HF) with reduced ejection fraction, thus pharmacists are valuable members of the multidisciplinary team approach to long‐term patient management. As pharmacists' scope of practice has expanded, growing evidence shows an evolution in pharmacists' roles in the care of patients with HF. To synthesize the literature describing implementation of pharmacist‐led medication titration and clinical assessments on outcomes in ambulatory patients with HF. MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…This policy statement described several key roles for pharmacists in the management of HF, including prevention of adverse drug reactions and medication errors, therapeutic drug monitoring, medication reconciliation, and medication adherence across the spectrum of HF management, both inpatient and outpatient 14 . Some HF clinics have begun incorporating pharmacist‐led HF medication optimization, including initiation and titration of evidence‐based therapies, which is supported by evidence of greater use of GDMT, and reductions in death and hospitalization 2,26,27 . Our consensus‐based list aligns with and expands upon this position statement, adding several evidence‐based activities in the medication management domain that leverage an expanding scope of practice and focus on the role that pharmacists can play independently and collaboratively to optimize medications for HF and common comorbidities.…”
Section: Discussionmentioning
confidence: 91%
“…This policy statement described several key roles for pharmacists in the management of HF, including prevention of adverse drug reactions and medication errors, therapeutic drug monitoring, medication reconciliation, and medication adherence across the spectrum of HF management, both inpatient and outpatient 14 . Some HF clinics have begun incorporating pharmacist‐led HF medication optimization, including initiation and titration of evidence‐based therapies, which is supported by evidence of greater use of GDMT, and reductions in death and hospitalization 2,26,27 . Our consensus‐based list aligns with and expands upon this position statement, adding several evidence‐based activities in the medication management domain that leverage an expanding scope of practice and focus on the role that pharmacists can play independently and collaboratively to optimize medications for HF and common comorbidities.…”
Section: Discussionmentioning
confidence: 91%
“…However, it is anticipated that pharmacy consult work will continue to grow because of accumulating evidence of positive clinical impacts of ambulatory pharmacists in the HF field. 4,7,8,[13][14][15][16][17][18] For example, the meta-analysis by McKay et al revealed that the 30-day all-cause readmission rate in the pharmacist-led transitions of care clinic was lower than the standard-of-care clinic in patients with congestive HF. 15 Another study by Davis et al found that a pharmacist-led clinic optimized sacubitril/valsartan and significantly reduced hospitalization for HF from 24.3% to 8.6% (P = 0.003) during the 12-month follow-up in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests pharmacist-led medication optimization in HF has improved medication adherence and guidelinedirected medical therapy (GDMT) as well as decreased hospitalization rates for HF. [3][4][5][6][7][8] In addition to improvements in clinical outcomes, a recent prospective observational study has demonstrated an annual total savings of $830,748 ($149,566 from clinical interventions and $681,182 from patient direct out-of-pocket expense reduction) with the addition of a cardiology clinical pharmacy specialist in a preventive cardiology practice. 9 Thus, pharmacists are integral to optimizing population health through better patient management and allocation of resources.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy to facilitate this goal is to include a pharmacist or a nurse to help educate and monitor patients and to optimize medications. 20,21 This example also included a mix of in-person and telephone patient encounters. Virtual or telephone visits can be a suitable format for initiating medications (eg, MRAs, SGLT2Is), titrating medications, and following up with patients whose HF is stable, who have demonstrated the ability to assess their HF symptoms, and who have tools at home to facilitate this (eg, weigh scale, BP monitor).…”
Section: Bringing Evidence To Practicementioning
confidence: 99%